PEMBUATAN MINUMAN KESEHATAN PENINGKAT IMUNITAS DARI TANAMAN TEMULAWAK (Curcuma xanthorryza) DI KORONG TAROK KAPALO HILALANG KABUPATEN PADANG PARIAMAN - Netty Suharti; Dira Hefni; Meri Susanti (Jurnal Hilirisasi IPTEKS, 2023)
After the Covid-19 pandemic in recent years which has caused many victims and hampered various activities in the community as well as fears of a decline in public health conditions, attention in increasing awareness and understanding of healthy living needs to be intensified by various parties including from universities. Socialization activities for a healthy way of life and efforts to increase the body's immunity against disease in the community and the use of natural plant materials to boost the immune system are the main concerns for staying healthy during and after a pandemic. The purpose of this activity is to assist the people of Korong Tarok Kapalo Hilalang, Padang Pariaman Regency, in utilizing and processing temulawak (Curcuma xanthorryza) to make an immunity-boosting health drink. This activity was carried out using two methods, (1) counseling or socialization of the temulawak plant which is useful as an immunity enhancer and (2) training on processing it into a health drink in the framework of self-medication in maintaining health independently. This activity was attended by the local community. Through this activity the community can understand and be able to process and utilize the temulawak plant into preparations in the form of health drinks independently. The community looked very enthusiastic and enthusiastic in participating in this activity. This activity can encourage the community to be able to implement healthy living behaviors by developing and optimizing the use of ginger medicinal plants in the environment into instant health drink preparations.